Reator de leito estruturado com recirculação submetido à aeração intermitente no tratamento de esgoto sanitário - Correa, Camila Zoe (2015)
The release of nitrogen compounds in water bodies can result in many environmental problems, so treat wastewater, such as sewage in order to remove not only organic matter but also nitrogen has been studied a few decades. From the above, the objective of this study was to evaluate the performance of a structured bed reactor, continuous flow, with recirculation, in removing organic matter and nitrogen present in wastewater under different cycles of intermittent aeration (AI) and to evaluate the influence of these cycles in the development of nitrifying bacteria (Oxidizing Bacteria Ammonia - BOA and Bacteria Oxidizing Nitrite - BON) and denitrifying (DESN) adhered (Support Material - MS) and suspension (Effluent - EF and sludge - LD). The reactor used has usable volume of 9.4 L. As support materials (MS) polyurethane foam was used, cut and fixed in PVC rods. 3 were worked aeration phases (AE) and non-aeration (AN) at different stage: Stage 1 (4 h EA / AN 2H); Stage 2 (2H EA / AN 1 h) and Phase 3 (2H EA / AN 2 h). During all hydraulic detention time phases was kept at 16 h and the effluent recirculated at a rate of 3 times the inflow. Were analyzed: pH, total alkalinity, temperature, chemical oxygen demand (COD), Biochemical Oxygen Demand (BOD), nitrogen Kjeldhl Total (NKT), ammonia-N-N-NH4+, nitrito-N-NO2+andnitrato-NO3-. The concentration of BOA, BON and DESN was determined using the number More Provável.gSSV-1 (NMP.gSSV-1). In phase 1 the percentage removal NTK N-NH4+ and NT was 76±10%, 70±21% and 67±10% respectively. In Phase 2 80±15% of removel NKT, 86±15% of N-NH4+ e 68±9% of removel NT e na Fase 3 de 58±20%, 72±28% and 41±6% of NKT, N-NH4+ of NT, respectively. The denitrification efficiency in stage 3 was over 70%, indicating that occurred in the reactor the process of simultaneous nitrification and denitrification (NDS). DQOT the removal percentages were 88 ± 4% in Phase 1, 94 ± 7 in Phase 2 and 90± 11% in Phase 3. The multivariate ANOVA applied to NMP.gSSV-1, it indicated that there was significant (F: 20,2, p <0,01) between the analyzed concentration of organisms AI in different cycles, but the differences between NMP.gSSV-1 depends not only isolated factors but of which means, and phase groups being analysis. From the results it is concluded that the working system is efficient in terms of nitrogen removal and organic matter, and that the stage with the highest availability of Dissolved Oxygen (DO) and C/N ratio (Step 2), was the one obtained the lower concentrations of organic matter effluents and N-NH4+. Hinted that there was a significant difference between the concentration (NMP.100mL-1) of the analyzed organizations (BOA, BON and DESN), but this difference does not depend on factors alone but of which means (MS, EF or LD), stages (1, 2 or 3) and groups (BOA, BON and DESN) is being considered.